Does REDW (Read, Examine, Decide, Write) Strategy Enhance Students’ Reading Comprehension? - Muslimaini Muslimaini; Wahyuni Fitria (IJER (Indonesian Journal of Educational Research), 2017)
The objectives of this study were to determine whether or not there was a significant effect of using REDW ( Read, Examine, Decide, Write ) strategy on reading comprehension and to know the significant difference of reading comprehension between students who are taught by using REDW (Read, Examine, Decide, Write) strategy and those who are not . The study was conducted at Islamic Junior High School Tarbiyah Islamiyah Jambi. The population in this study were all eighth graders, each class consisted of less than 30 students. The researcher used REDW strategy in class 8B as the experimental class and class 8A used conventional method as control class. This research used quantitative – experimental approach. The design of study was quasi-experimental design, it was the pretest-posttest non- equivalent group design. The data was collected by a test as research instruments, there were two test: pre-test and posttest. From the results of the test, the independent t-test calculation in posttest score in both groups showed that the significant value was higher than level of significance (0.870 > 0.05). It indicated that there was the significant difference between experimental and control group. Moreover, the paired t-test calculation showed the result of paired sample t-test (5.949 < 0.05) in which there was a significant effect of using REDW strategy on students reading comprehension.